Time Management Implementation in Daily Activities During Pandemic - Annisa, Vera Nur; Nandiyanto, Asep Bayu Dani; Kurniawan, Tedi; Bilad, Muhammad Roil (Indonesian Journal of Multidiciplinary Research, 2022)
During the Covid-19 pandemic, education requires online learning. The online system is a solution for Education in teaching and learning practices. The purpose of this study was to determine the understanding of elementary school students about the implementation of time management in daily activities during the pandemic. The research method used is quantitative, with a sample of 16 respondents from a population of 33 students. The results of the study show that there are still not many students who understand time management. With the presentation of learning in the form of videos, students' understanding in listening and curiosity increases. The results obtained that the number of pre-tests was only 74.39%, after being given the material and post-test the questionnaire increased to 94.25%.